An approach to auxiliary code generation for mobile environment: a case study of thrift-based codes conversion. (28th January 2020) - Qiu, Binyang; Zou, Qiming
In the development of mobile applications based on location information, system development for multisegment path planning and distant monitoring sites is complex. Developers are required to manually write inbound and outbound trigger functions for each site after multiple integrations of the planning results for a single route. In addition, each time that the route is changed, the developer needs to re-plan and re-bind the trigger function. This paper proposes an auxiliary code generation method based on the thrift application. Based on this method, a system for automatically generating code through visual design is designed, and an example of generating auxiliary development code for an application (APP) is implemented. Thrift provides multilanguage code generation services and implements a predefined point of interest (POI) recommendation service for real-time returned location information. This approach improves the efficiency of application (APP) development and also provides the ability to respond to changing process requirements.